Pelatihan dan Pemanfaatan Dashboard Pengelolaan Persediaan pada Peralatan Penunjang Kegiatan Belajar Mengajar - Muttaqin, Prafajar Suksessanno; Sumargo, Seto; Nurdiansyah, Yodi; Ferdin, Muhammad; Luzainnisa, Hanny; Sukmawati, Syifa Intan (Prima Abdika: Jurnal Pengabdian Masyarakat, 2024)
Education is a shared responsibility among families, the government, and the community. Every child has the right to receive good education, including moral education, social education, emotional education, intellectual education, and skill education. TK Negeri Pembina 1 is one of the public kindergartens located in North Cikarang, Bekasi Regency, West Java. TK Negeri Pembina is managed and directly supervised by the Bekasi Regency Education Office. The current issue faced is the disparity between the planned and actual quantities of teaching aids used in teaching and learning activities. For instance, consumable items like paper, markers, colored pencils, and other teaching aids. This disruption affects the teaching and learning process, ranging from restructuring groups and the number of student members to teachers purchasing items outside the established mechanism, resulting in increasing additional costs. Based on this issue, the community service team of the Bachelor of Engineering in Logistics or Digital Supply Chain program, where inventory management and information system design are areas of study, aims to contribute to society. The method used in this community service activity employs a training approach, where information, skills, or knowledge are conveyed to school teachers, the participants of the training. The hope is that this community service activity can provide benefits such as effective and efficient management of teaching aids inventory and transparency. The result of the community service activity is the improvement of the educational implementers' abilities in managing the inventory of teaching aids.